Arteriovenous Malformation and Papilledema - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 2004)
Two patients, ages 13 and 14, who presented with papilledema were found to have arteriovenous malformations (AVM) in a report from University College, London, UK.